About improving existing measurement methods in networks of digital terrestrial television broadcasting - A. A. Yanin (Известия высших учебных заведений России: Радиоэлектроника)
Modern methods and means of measurement used in the Russian digital terrestrial television networks are considered. New methods for improving the efficiency and objectivity of measurements in digital television proposed.